2015
DOI: 10.1016/j.ejmech.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of 6-substituted indolizinoquinolinediones as catalytic DNA topoisomerase I inhibitors

Abstract: In our previous work, indolizinoquinolinedione derivative 1 was identified as a Top1 catalytic inhibitor. Herein, a series of 6-substituted indolizinoquinolinedione derivatives were synthesized through modification of the parent compound 1. Top1 cleavage and relaxation assays indicate that none of these novel compounds act as classical Top1 poison, and that the compounds with alkylamino terminus at C-6 side chain, including 8, 11–16, 18–21, 25, 26 and 28–30, are the most potent Top1 catalytic inhibitors. Top1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…3, hippeastrine and camptothecin exhibited inhibitory activity on Top I in a similar dose-dependent manner with the IC 50 values at 7.25 ± 0.20 μg/mL and 6.72 ± 0.23 μg/mL, respectively, which clearly implied that hippeastrine was found to be comparable with the well known anticancer drug camptothecin in terms of IC 50 . Other tests on camptothecin against Top I also showed similar inhibitory activity levels with the IC 50 values at 8.71 μg/mL35 or 8.53 μg/mL36, which could further approve our finding in this work. Hence, our result confirmed that hippeastrine could be a potential Top I inhibitor as a very promising anticancer drug candidate, which is in good consistent with the enrichment factors based on UF-LC/MS assay and provides a good validation for its effectiveness.…”
Section: Resultssupporting
confidence: 86%
“…3, hippeastrine and camptothecin exhibited inhibitory activity on Top I in a similar dose-dependent manner with the IC 50 values at 7.25 ± 0.20 μg/mL and 6.72 ± 0.23 μg/mL, respectively, which clearly implied that hippeastrine was found to be comparable with the well known anticancer drug camptothecin in terms of IC 50 . Other tests on camptothecin against Top I also showed similar inhibitory activity levels with the IC 50 values at 8.71 μg/mL35 or 8.53 μg/mL36, which could further approve our finding in this work. Hence, our result confirmed that hippeastrine could be a potential Top I inhibitor as a very promising anticancer drug candidate, which is in good consistent with the enrichment factors based on UF-LC/MS assay and provides a good validation for its effectiveness.…”
Section: Resultssupporting
confidence: 86%
“…Since deletion of Top1 did not unsilence Ube3a , whereas topotecan (which forms TOP1cc’s) did unsilence Ube3a , we hypothesized that TOP1cc’s may be required to unsilence Ube3a in neurons. To test this hypothesis, we compared topotecan to a series of TOP1 catalytic inhibitors that inhibit TOP1 without forming TOP1cc’s ( S5A Fig ) [ 28 , 29 ]. As previously found [ 13 ], topotecan unsilenced the paternal Ube3a-YFP allele in Ube3a m+/pYFP cortical cultures ( S5B and S5C Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…As previously found [ 13 ], topotecan unsilenced the paternal Ube3a-YFP allele in Ube3a m+/pYFP cortical cultures ( S5B and S5C Fig ). However, paternal Ube3a-YFP was not unsilenced after treating with four different TOP1 catalytic inhibitors, including CYB-L10 [ 29 ], over a range of doses ( S5B and S5C Fig ). CYB-L10 did significantly reduce expression of synaptic adhesion molecules in wildtype cells ( S5D and S5E Fig ), suggesting the drug can enter cells and reduce expression of genes that are affected by Top1 deletion.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, CPT derivatives are expected to have improved solubility and stability. Yu et al (18) synthesized a series of 6-substituted indolizinoquinolinedione derivatives and evaluated them for their biochemical and biological activities. Zhou et al (28) evaluated the cytotoxicity of MXN-004 (a small-molecule compound of PEGylated SN38) in vitro and demonstrated that it has good water solubility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the CPT-11 prodrug group (4-piperidinyl piperidine) causes AchE inhibition, which easily leads to acetylcholine syndrome, resulting in early severe diarrhea and other sideeffects (10). In order to overcome the above drawbacks of CPT-11, scientists have made several attempts to improve it (10,(17)(18)(19). In the present study, we designed and synthesized a novel 10-hydroxy CPT prodrug with a high efficiency and low toxicity (20,21).…”
Section: Antitumor Potential Of a Novel Camptothecin Derivative Zbh-mentioning
confidence: 99%